A Study On Academic Dishonesty Among University Students: The Implementation Of University Policy And Students’ Awareness On Academic Dishonesty - Hamdzah, Nor Lailatul Azilah; Sidek, Safiah; Zainal Abidin, Nadiah; Hanafi, Zulkifli; Hassan, Ruslan (Penerbit Universiti Teknikal Malaysia Melaka, 2020)
This study discusses the findings on academic dishonesty among Malaysian university students. In this study, the level of key variables is explored; the students’ awareness on academic dishonesty, the implementation of academic policy and the students’ involvement in academic dishonesty. A total of 389 tertiary level students which comprised of 72 males and 217 females from a university in Malaysia were the samples of this study. The study used quantitative methods. The questionnaire was used as the study instrument for academic dishonesty among university students. From the findings, the study indicates that there is a significant difference in the effects of Programme types on the level of the students’ involvement in committing academic dishonesty for male students and female students. An implication of the study is discussed and suggestions are advanced.